2018
DOI: 10.1017/s0950268817003132
|View full text |Cite
|
Sign up to set email alerts
|

Web survey-based selection of controls for epidemiological analyses of a multi-prefectural outbreak of enterohaemorrhagicEscherichia coliO157 in Japan associated with consumption of self-grilled beef hanging tender

Abstract: An outbreak of enterohaemorrhagic Escherichia coli O157 occurred in multiple prefectures of Japan in November 2009. We conducted two case-control studies with trace-back and trace-forward investigations to determine the source. The case definition was met by 21 individuals; 14 (66.7%) were hospitalised, but no haemolytic uraemic syndrome, acute encephalopathy or deaths occurred. Median age was 23 (range 12-48) years and 14 cases were male (66.7%). No significant associations with food were found in a case-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Background exposure data from food consumption surveys can be applied for binomial probability analyses, a method that was developed at Oregon Health Authority [40]. Besides food consumption survey data, market share data [41], shopping card or till receipt information [42] and data from market-research panels [43][44][45] have been used in outbreak investigations. We consider our food consumption survey an additional helpful tool for outbreak investigations in Germany.…”
Section: Discussionmentioning
confidence: 99%
“…Background exposure data from food consumption surveys can be applied for binomial probability analyses, a method that was developed at Oregon Health Authority [40]. Besides food consumption survey data, market share data [41], shopping card or till receipt information [42] and data from market-research panels [43][44][45] have been used in outbreak investigations. We consider our food consumption survey an additional helpful tool for outbreak investigations in Germany.…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment challenges are not unique to case-control studies, and other types of observational studies have shifted from traditional telephone interviews to web-based surveys with the goal of reaching larger groups of people more efficiently and at a lower cost [ 7 - 12 ]. While offering some advantages over traditional telephone interviews, web-based surveys often experience lower response rates and lower data quality [ 13 ], and some studies have found demographic differences between telephone and web-based survey participants, likely driven in part by disparities in internet connectivity and access [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are frequently used by marketing companies or polling organizations to obtain information about a target audience. Commercial online panels have successfully been used to collect epidemiological exposure data in retrospective (15) and prospective case-control studies (16)(17)(18)(19)(20)(21). One of the key benefits of this approach is that it allows efficiently and rapidly recruiting many controls, therefore enabling timely investigation of outbreaks.…”
Section: Introductionmentioning
confidence: 99%